Atherothrombosis in South Asians: Implications of Atherosclerotic and Inflammatory Markers - Dodani, Sunita (Bentham Open, 2010)
South Asian immigrants (SAIs) have a higher prevalence of cardiovascular (CV) morbidity and mortality compared with other populations. The major challenge associated with primary prevention of cardiovascular to coronary artery diseases (CAD) in SAIs involves early and accurate detection of CAD in asymptomatic individuals at high cardiovascular risk. Inflammatory processes are now recognized to play a central role in the pathogenesis of atherosclerosis and are found to be associated with future CV risk in a variety of clinical settings. Imaging measures, such as common carotid artery intima-media thickness (CCA-IMT), are being applied as surrogate markers for end-points, such as myocardial infarction (MI) and death in clinical trials. Considering high CAD risk in SAIs and knowing that conventional risk factors may not fully explain the excess CAD risk in this group, studies on the role of CCA-IMT in CAD prediction have been discussed. Also, C-reactive protein (CRP) validity in risk prediction, the role of dysfunctional high density lipoprotein (HDL) as a CAD risk marker in SAIs have been presented.